Prevalence and influencing factors of subjects at high risk for cardiovascular disease in different regions of Gansu province, China: a cross-sectional study of 100,725 residents from 2017 to 2022 - Li, Yixuan; Zhang, Chouji; Chen, Faqing; Zhang, Jing (Frontiers in Cardiovascular Medicine, 2024)
Background To investigate the prevalence rate of subjects at high risk for cardiovascular disease (CVD) and to analyze the influencing factors in different regions of Gansu Province. Methods We used data from the China Patient-centered Evaluative Assessment of Cardiac Events (PEACE) Million Persons Project (MPP), which screened 100,725 residents aged 35–75 years from 10 project sites in Gansu Province, China, from 2017 to 2022. In addition, a questionnaire survey, anthropometric measurements, and collection of biological samples were carried out. Results Of the 100,082 residents included, 21,059 were identified as subjects at high-risk for CVD. The overall prevalence rate of subjects at high risk for CVD was 19.7%, and the prevalence rate in the HeXi region was greater than that in the LongZhong and LongDong regions. The prevalence rates were 14.0%, 58.2%, 34.9%, and 5.7% for cardiovascular history, hypertension, dyslipidemia, and WHO-assessed risk ≥20%, respectively. The prevalence rate of cardiovascular history type was the highest in the HeXi region, hypertension and dyslipidemia types were the highest in the LongZhong region, and WHO-assessed risk ≥20% type was the highest in the LongDong region. Male, higher education level, smoking status, snoring status, overweight and obesity status, central obesity status, and disease history were more likely to be risk factors for subjects at high risk for CVD. There were some differences among different regions in age, annual household income, farming status, rural/urban status, and drinking status. Conclusion The prevalence rate of subjects at high risk for CVD in Gansu Province is relatively high. Individualized intervention measures as well as comprehensive prevention and control strategies should be adopted, focusing on the distribution characteristics of risk factors among high-risk subjects in different regions.